The family Corleone - Falco, Edward
New York, 1933. The crime families have prospered in the Depression, but with the coming end of Prohibition a battle is looming... one which will determine which organizations will rise, and which will face a violent end. Vito Corleone pushes his oldest child, teenaged Sonny, to be a businessman. But Sonny-- impatient and reckless-- wants to become a part of the real family business.